TYPOLOGY OF SUBCULTURES: ACTIVITY AND COMMUNICATION (Philological Studies, 2019)
The article presents a typology of subcultures based on the major activity type of its members and on the mediation of their communication by modern computer technologies. The proposed classification of subcultures takes into account the following features: 1) the activity of a social group is/is not its major activity (professional activity); 2) the activity of a social group refers/does not refer to a certain specific (professional) domain; 3) group members are active participants of the activity/group members are observers and commentators of the activity; 4) computer technologies are the basis for a subculture/a subculture can exist without computer technologies; 5) the Internet is widely used for communication by group members/ the Internet is not an obligatory part of communication. Taking into account the above-mentioned five features, 32 types of subcultural formations are distinguished.
Keywords: subculture, classification, activity type, type of communication, classification basis